SIFAT FUNGSIONAL TEPUNG KORO KRATOK HITAM, MERAH DAN PUTIH (Phaseolus lunatus L.) DENGAN PERLAKUAN LAMA PERENDAMAN (Functional Properties of Black, Red and White Lima Bean (Phaseolus lunatus L.) Flour Produced under Different Soaking Time) - Diniyah, Nurud; Windrati, Wiwik Siti; Maryanto, Maryanto (Jurnal Hasil Penelitian Industri, 2015)
The aim of this research is to determine technical functional characteristics of the varietieslima bean seed flour (black, red, and white) with different treatment soaking time (12, 24 and 36 hour).Parameter of emulsion activity and stability, foam activity and stability, OHC (Oil Holding Capacity),WHC (Water Holding Capacity) and viscosity are investigated. The results showed that white lima beanseed flour with 12 hour soaking time have the highest emulsion activity and stability (164,28 m2/g; 4,39jam); foaming activity and stability, OHC and WHC of the varieties lima bean seed increased withincrease in soaking time. While, viscosity showed constant value for all varieties of lima bean seed flour.